STRUKTUR MUSIK IRINGAN TARI BAKONCONG PADA SUKU DAYAK BADAMEA DESA SENATAB KECAMATAN SAJINGAN BESAR KABUPATEN SANBAS - Toto, Widina Karma; Ismunandar, Ismunandar; Silaban, Chiristianly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis background of this researchers to find musical structures accompanied by Bakoncong dance of the Badamea Dayak tribe of Senatab Village, Sajingan Besar District, Sambas Regency. The problem of this research were